The Nested Knowledge System of TPACK: A Case Study on Physics Teachers' Educational Resource Selection and Integration - Bassel Chazbeck; Zalpha Ayoubi (Journal of Education in Science, Environment and Health)
The aim of this research is to explore the system of knowledge of the Lebanese secondary physics teachers that affects the selection and integration of educational resources. This teachers' knowledge was studied through their pedagogical and technological pedagogical content knowledge (PCK and TPCK) concerning instructional strategies, students understanding, curricula, and curriculum materials, including technology that is mobilized in their practice. For this aim, a qualitative approach was employed, and four physics teachers purposefully selected from four secondary schools participated in this study. Classroom observations and interviews were used as research data collection tools. The data analysis revealed that the system of the different teachers' knowledge studied in this research could be seen as a whole, while one system of knowledge was highly related to another. This study, hence, called these consistent knowledge systems "nested knowledge system." This study also showed that this "nested knowledge system" determines teachers' didactical decisions in general and influences the selection and integration of resources in particular. It also revealed that misconceptions are persistent and cannot be changed easily. Moreover, the context of the teaching-learning process reshapes the teacher's knowledge about students' understanding, which is the only knowledge that shows inconsistency between intended and operational practice. In addition, it showed that teachers' knowledge about students' understanding (PCK/U) has a significant effect on teachers' knowledge about curricula and instructional strategies (TPACK/C & TPACK/S).